Morning and evening salivary melatonin, sleepiness and chronotype: A comparative study of nurses on fixed day and rotating night shifts. (23rd September 2020) - Bani Issa, Wegdan; Abdul Rahman, Hanif; Albluwi, Najila; Samsudin, A. B. Rani; Abraham, Suma; Saqan, Roba; Naing, Lin
Abstract: Aims: To compare morning and evening salivary melatonin levels, sleep quality and chronotype between nurses working fixed day shifts and those working rotating night shifts. Background: Rotating night shift work is an inevitable part of nursing and is a major reason for disrupted sleep. Design: Cross‐sectional comparative design. Participants and Settings: We used cluster sampling to recruit 520 female nurses working fixed day and rotating night shifts in the United Arab Emirates. Methods: Morning and evening melatonin were measured from corresponding saliva samples. The Pittsburgh Sleep Quality Index used to evaluate sleep quality and self‐assessment of preferred circadian times was used to assess participants' chronotypes. Data were collected between October 2017–December 2018. Results: Rotating night shift nurses had significantly lower evening melatonin compared with the fixed day shift group. No significant difference was found in sleep quality between the groups, although more participants in the rotating night shift group ( N = 110, 42.31%) expressed better sleep quality than those in the fixed day group ( N = 90, 36.00). Participants in the rotating night shift group expressed better subjective sleep, longer sleep duration, less disturbed sleep and better daily function ( p > .05) than the fixed day group. Rotating night shift participants were more likely to have evening or intermediate chronotypes and more likely to report alignment of shift work to their chronotype compared with fixed day shift participants ( p = .001). Longer shift duration, marital status and city location were associated with reduced evening melatonin among nurses on rotating night shifts. Conclusion: Rotating night shift nurses showed evidence of better sleep than those from the fixed day shift. Proper shift assignment, chronotype and alignment with shift work appeared to produce better sleep quality. Impact: Organizational policy must consider a novel model for work schedules that allow adequate off‐duty days for sleep recovery among nurses. 摘要: 目的: 比较固定白班和轮值夜班护士的早晚唾液褪黑素水平、睡眠质量和作息类型。 背景: 轮值夜班工作是护理工作中不可避免的, 也是影响睡眠的一个重要原因。 设计: 横截面对比研究。 受试者和环境: 我们采用整群抽样方式, 在阿联酋招募了520名固定日班和轮值夜班的女护士。 方法: 从相应的唾液样本中测量早晚褪黑素。睡眠质量评估用匹兹堡睡眠质量指数和首选昼夜时间自我评估用于评估受试者的作息类型。数据收集时间为2017年10月至2018年12月。 结果: 与固定白班护士相比, 轮值夜班护士的晚间褪黑素显著降低。尽管轮值夜班组受试者(N=110, 42.31%)比固定日班组受试者(N=90, 36.00)的睡眠质量更好, 但组间睡眠质量没有显著差异。与固定日班组受试者相比, 轮值夜班组受试者表示主观睡眠质量更好, 睡眠时间更长, 睡眠干扰更少, 日常生活功能更好(P>.05)。与固定日班组受试者相比, 轮值夜班组受试者更有可能具有晚间或中间作息类型, 更有可能报告轮班工作与他们的作息类型一致(p=.001)。在轮值夜班护士中, 晚间褪黑素的减少与较长的轮班时间、婚姻状况和城市位置有关。 结论: 轮值夜班护士的睡眠质量优于固定日班护士的睡眠质量。适当的轮班制度、作息类型以及与轮班工作的一致性似乎能产生更好的睡眠质量。 影响: 组织政策必须考虑一种新的工作时间模式, 该模式使得护士有足够的非工作日进行睡眠恢复。